Modified Asphalt Mix Performance With The Addition Of Human Hair Waste - Zulfikar, Zulfikar; Lakawa, Irwan; Sulaiman, Sulaiman; Hawa, Sitti (Universitas Sulawesi Tenggara, 2022)
The development of road infrastructure in Indonesia is currently increasing, starting with new road construction projects to road improvement projects. To prevent premature damage to road pavements due to loading and the influence of water, it is to improve the quality of asphalt as a binder material from aggregate in the composition of road pavements. especially for the Asphalt Concrete-Binder Course (AC-BC) mixture, the addition of human hair waste can be used as an added material to minimize the use of asphalt and overcome the weaknesses of asphalt and waste utilization.The objectives of the study were: (1) to analyze the characteristics of the modified asphalt mixture with the addition of human hair waste. (2) Analyzing the performance of modified asphalt mixture with the addition of human hair waste.The results of analysis and testing in the laboratory show that the modified asphalt mixture performance with the addition of hair will increase the density value up to 2,355 gr/cc, increase the stability value up to 1886,2 kg, increase the value of the asphalt filled cavity (VFB) up to 82.8% and increase the Marshall value. Quotient (MQ) up to 653.3 kg/mm, but will reduce the value of the melt (flow) up to 2.9 mm, reduce the value of voids between mineral aggregates (VMA) up to 15.8% and reduce the value of mixed air voids (VIM) up to 2.7% but still within the threshold of meeting specifications